The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17925/enr.2015.10.02.189
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone as a Novel Therapeutic Approach for Duchenne Muscular Dystrophy

Abstract: Progressive loss of pulmonary function leads to early morbidity and mortality in Duchenne muscular dystrophy (DMD) due to both expiratory impairment with ineffective airway clearance, and inspiratory impairment leading to nocturnal and daytime hypoventilation and respiratory failure. Glucocorticoid steroids have become a mainstay of DMD therapy with well-documented efficacy on muscle strength and respiratory function. However, the side-effect profile restricts their long-term use, particularly in non-ambulant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In the Mc-Donald et al [30] study, boys 10-20 years of age who were not on GC showed a decline in FVC of 8.5%/year. Similarly, in a placebo arm of a clinical trial, FVC%p declined 8.7% in a largely non-ambulant cohort of glucocorticoids non-treated patients with mean age of 15.0 ± 2.5 [9,38] . Hahn and colleagues studied 7-25 year olds and measured a 7.9% decline [39] .…”
Section: Absolute Fvc and Fvc%pmentioning
confidence: 94%
See 1 more Smart Citation
“…In the Mc-Donald et al [30] study, boys 10-20 years of age who were not on GC showed a decline in FVC of 8.5%/year. Similarly, in a placebo arm of a clinical trial, FVC%p declined 8.7% in a largely non-ambulant cohort of glucocorticoids non-treated patients with mean age of 15.0 ± 2.5 [9,38] . Hahn and colleagues studied 7-25 year olds and measured a 7.9% decline [39] .…”
Section: Absolute Fvc and Fvc%pmentioning
confidence: 94%
“…FVC, and PEFr may be reliably measured in DMD patients older than age 6 [4][5][6] . Measurement of pulmonary function in DMD including spirometry, static airway pressures and their relationship to diaphragmatic and chest wall weakness and fibrosis has been reviewed in detail elsewhere [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Idebenone, a synthetic short-chain benzoquinone, improves mitochondrial function, restores ATP production and catalytically reduces reactive oxygen species, thereby addressing the muscle cell damaging consequences of dystrophin deficiency (as reviewed in [12] ). Idebenone showed a cardio-protective effect and improved exercise performance in the dystrophin-deficient mdx mouse model of DMD [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the development of antioxidants for the treatment of DMD has been a substantial line of research with numerous compounds investigated, e.g. coenzyme Q 10 , catalase, green tea extract, Epigallocatechin gallate, BN82270, Idebenone, melatonin and N-acetylcysteine [ 14 , 43 – 49 ]. Mitochondrial Ca 2+ overload is known to promote ROS generation and membrane permeability in healthy muscle [ 13 , 50 ].…”
Section: Discussionmentioning
confidence: 99%